Cooperative Stapling of Native Peptides at Lysine and Tyrosine or Arginine with Formaldehyde. (12th February 2021) - Li, Bo; Tang, Hong; Turlik, Aneta; Wan, Zhao; Xue, Xiao‐Song; Li, Li; Yang, Xiaoxiao; Li, Jiuyuan; He, Gang; Houk, Kendall N.; Chen, Gong
Abstract: Stapling of peptides by intramolecular crosslinking of two neighboring amino acid side chains offers an important tool to modulate the structure and properties of peptides. In comparison to the stapling of artificially engineered peptide substrates, methods for stapling native peptides are more desirable for easier accessibility and genetic encodability. However, the existing strategy for selectivity control in the stapling of native peptides is relatively limited: the site of anchoring is often dominated by Cys, and the means for achieving the position selectivity among the same type of residues at different locations is lacking. We have developed a simple and powerful strategy for stapling native peptides at lysine residues with formaldehyde by the cooperation of nearby tyrosine or arginine residues. The stapling reactions can proceed with high efficiency and residue selectivity under mild conditions, and generate linchpins with distinct physiochemical properties. The new method for peptide stapling enables unique control of position‐selectivity for substrates bearing multiple reaction sites by reactivity that can be readily built in the peptide sequence. Abstract : A cooperative strategy for stapling native peptides at lysine and nearby tyrosine or arginine residues with formaldehyde is reported.